2008
DOI: 10.1007/s10557-008-6116-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Initial 6 Months Monotherapy with Bisoprolol versus Enalapril in the Treatment of Patients with Mild to Moderate Chronic Heart Failure. Data from the CIBIS III Trial

Abstract: Bisoprolol and enalapril had a similar effect on the combined end-point of mortality or hospitalization during 6 months monotherapy. However, more worsening HF events were observed in the bisoprolol group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Although this finding depends on a single trial, PARADIGM-HF was the largest trial in the network, representing 18 898 patient-years of treatment exposure. 7 It is also important to note that although BB monotherapy is included in the network and, therefore, can be compared with other monotherapies using NMA, data to support this comparison are based on 2 small, short-duration trials (CIBIS III [Cardiac Insufficiency Bisoprolol Study III] 46 and CARMEN trial [Carvedilol and ACE-Inhibitor Remodelling Mild Heart Failure Evaluation] 47 ). The majority of available evidence regarding the efficacy of BB therapy is based on studies where patients were also receiving an ACEI (and MRA in more recent trials).…”
Section: Discussionmentioning
confidence: 99%
“…Although this finding depends on a single trial, PARADIGM-HF was the largest trial in the network, representing 18 898 patient-years of treatment exposure. 7 It is also important to note that although BB monotherapy is included in the network and, therefore, can be compared with other monotherapies using NMA, data to support this comparison are based on 2 small, short-duration trials (CIBIS III [Cardiac Insufficiency Bisoprolol Study III] 46 and CARMEN trial [Carvedilol and ACE-Inhibitor Remodelling Mild Heart Failure Evaluation] 47 ). The majority of available evidence regarding the efficacy of BB therapy is based on studies where patients were also receiving an ACEI (and MRA in more recent trials).…”
Section: Discussionmentioning
confidence: 99%
“…The 4 studies with the highest risk of bias were not double-blinded, which might have introduced bias. [3][4][5][6] However, when excluding these 16 studies, our results do not meaningfully change (Figure 1). The most significant difference is seen in digoxin studies.…”
mentioning
confidence: 75%
“…Clinical trial results showed that β-ABs has a positive effect on the clinical course of HF and reduces the risk of five-year mortality by 30% [12,24,25]. In Recommendations of the European Society of Cardiologists (ESC) [14] and the American College of Cardiologists and the American Association of Cardiologists (ACC / ANA) [26] it is emphasized that β-ABs are a first-line drug for the treatment of patients with HF.…”
Section: Discussionmentioning
confidence: 99%